ARRHYTHMIA IN ACUTE CORONARY SYNDROME: MINI REVIEW - Sidhi Laksono; Natasha Anindhia Harsas (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2022)
Acute coronary syndrome is a life-threatening disease often accompanied by manifestations of arrhythmias. Tachyarrhythmias of supraventricular and ventricular origin are common in the early hours and at reperfusion. This condition can worsen the patient's prognosis and might result in sudden death if not treated quickly and appropriately. Conduction disorders are also one of the complications that occur due to ischemia in the heart. The treatment given is not only aimed at saving the patient during the acute phase. However, therapy for risk factor modification and prevention of recurrent acute events is also important to increase long-term survival. In this literature review, we will discuss recommendations for pharmacological and non-pharmacological management of arrhythmias in cases of acute coronary syndrome in emergency and follow-up situations with various patient characteristics and forms of arrhythmias that appear.